The Oxford history of Anglicanism, volume V : global Anglicanism, c. 1910-2000 - Sachs, William, ed. (Oxford : Oxford University Press, 2017)
Volume five of The Oxford History of Anglicanism considers the global experience of the Church of England in mission and in the transitions of its mission Churches toward autonomy in the twentieth century.
Anglican social ministries in East Asia/ John Y.H. Yieh
Includes bibliographical references and index.
Keywords: Anglican Communion -- History -- 20th century